Real neutral interest rate and international financial reporting standards - Arrarte Mera, Raúl Alberto (2018)
This paper sponsored by San Marcos´s National University, is exploratory-descriptive-quantitative based on the construction of increasing and decreasing future revenues flows at low and high interest rates, that is, a mathematical simulation; Objectives: To evaluate how to establish a neutral discount factor, in Latin America and the Caribbean, to apply to international financial reporting standards. Verify how to estimate a neutral real interest rate. To study whether a normalized and transparent neutral real interest rate contributes to the fight against money laundering and corruption. It is concluded that, in both the emerging and non-emerging countries, the efficient use of macroeconomic tools is rewarded with low interest rate; on the other hand, higher interest rates are applied to countries with higher inflation rates due to the poor management of their economy. We confirm that it is convenient for our countries that the Peru´s Central Bank and other related entities in Latin America and the Caribbean should normalize quarterly real interest rates at the regional level using the two official languages of the United Nations (UN): Spanish and English; Applying global criteria of recognized institutions such as: Federal Reserve of the United States of America (FED), Central Reserve Banks of each country and J.P. Morgan Chase of New York risk ratings; based on a basket of tolls such as: basic Fed rate, inflation rates and / or devaluation, country risk, and administrative cost of money.